POTASSIUM FERTILIZATION ON THE PRODUCTION OF TWO MELON CULTIVARS - Bardiviesso, Diogenes Martins; Maruyama, Wilson Itamar; Pessato, Luis Eduardo [UNESP]; Bueno Pereira, Ana Carolina [UNESP]; Modesto, Joyce Helena [UNESP] (Univ Estadual Mato Grosso Sul, 2015)
aThe potassium fertilizer recommendations for the melon crop varies according to the region, and these recommendations are influenced by climate condition, soil and growing conditions. The objective of this study was to evaluate the effects of potassium rates on yield and fruit quality of two melon cultivars under field conditions in Cassilandia-MS. Treatments were arranged in a randomized block design in a 2 x 5 factorial: two cultivars [hybrid Yellow Giorgio (Cucumis melo var. Inodorus) and hybrid Cantaloupe Rafael (Cucumis melo var. cantalupensis)] and five K rates (0, 60, 120, 180 and 240 kg ha(-1) of K2O), with four replications. The K fertilizer rates were applied at planting and top-dressing in the form of granules. The fruit yield, weight, length and diameter of the fruits, bark thickness, degrees Brix and pulp pH, and percentage of commercial fruits were evaluated. The K fertilizer rate that provided the highest fruit yield of melon was 136.75 kg K2O ha(-1). The hybrid Yellow Giorgio produced fruits that meet the commercialization standards at appropriate levels.
Keywords: Cucumis melo; nutrition; potassium chloride